Enhanced Cooperation - the New Trend of the EU Development - Lyudmila O. Babynina (Vestnik MGIMO-Universiteta, 2014)
The article is dedicated to implementation of the enhanced cooperation in the EU. Actually two such projects are шn progress (the law applicable to divorce and legal separation and unitary patent protection) and other two are under discussionffmandai transaction tax and European Public Prosecutor's Office). Active use of the enhanced cooperation recently shows that such kind of the promoting integration is more and more required in the EU. However its implementation can jeopardize the principles of the EU functioning and undermine the status of the institutions in the integration process. This mechanism can also be used in order to exclude the discordant states from integration process instead of traditional search of compromises. This argument is based on analysis of the implementation conditions of the project on the unitary patent protection. At the same time the projects of the enhanced cooperation obviously make the interaction in different spheres more efficient. In addition they can be used for testing the new types of cooperation. That's why the search for an optimal balance between promotion integration through the mechanism of enhanced cooperation and preserving the unity of the EU should be considered as main goal by participants of the integration process. Otherwise the gradual separation on the vanguard group may lead to EU division. Nevertheless taking into consideration enlargement of the EU and its diversity, the enhanced cooperation Should be used onlyas "extreme measure".